Efektivitas teknik relaksasi dalam menurunkan tingkat kecemasan pada PMI di shelter KBRI Kuala Lumpur - Nurfatihah Dahlan; Sofa Amalia; Muhammad Fath Mashuri (Fakultas Psikologi, 2023)
The problems experienced by Indonesian migrant workers are very diverse, such as employment problems, neglect and so on. This can trigger anxiety so that handling efforts such as relaxation are needed. This study aims to test the effectiveness of relaxation in reducing anxiety levels in Indonesian migrant workers at the Shelter of the Indonesian Embassy in Kuala Lumpur. This study used a quantitative approach with a pre-experimental research design in the form of a one-group pretest-posttest design that measured adaptation to the Depression Anxiety Stress Scale (DASS-21). The population in this study were all PMIs with moderate to high levels of anxiety who were at the Indonesian Embassy in Kuala Lumpur, which were obtained using a purposive sampling technique. The data that has been obtained from the field is then processed by JASPO.16 (Jeffreys' Amazing Statistics Program) using Wilcoxon signed-rank test analysis. The results of this study indicate that the hypothesis is rejected, namely relaxation is not effective in reducing anxiety for Indonesian Migrant Workers who are in Shelters at the Indonesian Embassy in Kuala Lumpur, as seen from a probability of 0,098 (p > 0,05). The rank-biserial correlation (rB) as an effect size with a value of 1.000 > 0.5 indicates a large effect size. This research is a reference for the Indonesian Embassy in Malaysia in dealing with anxiety problems that are often experienced by PMI in Malaysia. Keywords: Anxiety, Indonesian migrant workers, relaxation